2023
DOI: 10.1002/sd.2818
|View full text |Cite
|
Sign up to set email alerts
|

Extended reality (XR)—A magic box of digitalization in driving sustainable development of the construction industry: A critical review

Hongyang Li,
Shuying Fang,
Long Chen
et al.

Abstract: Against a background of global resource shortage and climate change, there is an urgency for the construction industry to aim towards sustainable development. With the rapid development of information technology, the emergence of extended reality (XR) has provided new ideas and options for sustainable construction (SC). Such technologies are applied in research and practice of the whole construction lifecycle, which can well meet the requirements of SC. This paper presents a critical review of XR applications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…As shown in Table 3, which lists smart city technology applications in immersive technology and BIM in sustainable smart cities since 2014, case studies [6][7][8][20][21][22][23]31,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] are the most used method for integrating smart city in immersive technology, followed by literature reviews [6,7,9,19,31,39,[50][51][52][53][54], interviews [8,20,22,36,37,[43][44][45][46], questionnaires [8,20,22,36,37,[43]…”
Section: Sustainable Smart Citymentioning
confidence: 99%
“…As shown in Table 3, which lists smart city technology applications in immersive technology and BIM in sustainable smart cities since 2014, case studies [6][7][8][20][21][22][23]31,[36][37][38][39][40][41][42][43][44][45][46][47][48][49] are the most used method for integrating smart city in immersive technology, followed by literature reviews [6,7,9,19,31,39,[50][51][52][53][54], interviews [8,20,22,36,37,[43][44][45][46], questionnaires [8,20,22,36,37,[43]…”
Section: Sustainable Smart Citymentioning
confidence: 99%
“…Extensive research has been conducted on applications of XR in the built industry for use in various construction phases [18,19]. Applications of MR, in particular, facilitate decision-making in the pre-construction phase, as alternative designs can be projected onto existing spaces, enhancing communication [27].…”
Section: Xr Applications In the Aeco Industrymentioning
confidence: 99%
“…Specifically in the Architecture, Engineering, Construction, and Operations (AECO) industry, it was observed that 49% of the research focused on construction phase use cases such as site monitoring and inspections, construction simulations, training tools for assembly, and enhancing construction safety [18]. However, a recent study on XR applications for sustainable construction revealed that most use cases focus on the preconstruction stage [19]. The more prominent occurrence of use cases in the pre-construction stages can be attributed to the focus on sustainable construction, where decisions, such as the selection of sustainable materials, must occur during the pre-construction stages.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation